Pencegahan Stres Pada Ibu Dengan Anak Berkebutuhan Khusus Di SLB Negeri Ciamis - Ima Sukmawati; Yuyun Rahayu; Sri Utami Asmarani; Al Syifa Rosna Anggraini; Heni Marliany; Diny Nurfauziah (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2023)
Introduction: Having a child with special needs can be challenging for parents, especially mothers. Maternal stress can have a negative impact on the quality of life of children with special needs. Mothers with high stress tend to be authoritarian, abusive and interact negatively. High levels of stress can affect mothers' mental and physical health, so efforts need to be made to reduce these stress levels. Objective: The purpose of this activity is to prevent and reduce stress levels in mothers of children with special needs. Methods: This community service activity was carried out on 25 August 2023, located at SLB Negeri Ciamis, with 25 mothers who have children with special needs as respondents.  Methods in this counselling with 1) Identification of mothers who have children with special needs 2) Counselling 3) Evaluation and demonstration. Results: Based on the evaluation results in counselling activities regarding stress prevention in mothers who have children with special needs, it is found that mothers have understood the material provided by evaluating being able to answer the questions given and can demonstrate benson therapy independently.  Conclusion: Respondents are enthusiastic and understand the material provided, where respondents are able to answer questions given and are able to demonstrate benson therapy independently.